Crop genetic resources as a global commons: challenges in international law and governance - Halewood, Michael; López Noriega, Isabel; Louafi, S. (Earthscan, 2013)
This book addresses how the collective pooling and management of shared plant genetic resources for food and agriculture can be supported through laws regulating access to genetic resources and the sharing of benefits arising from their use. It also analyzes tensions that are threatening to undermine the potential of such laws, and identifies opportunities to address those tensions.